READING ANNA’S INSTABILITY AND FEAR OF ABANDONMENT IN ANNA KARENINA - Diva Wenanda (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2022)
This study found that the personality disorder suffered by Anna is borderline personality disorder. This study is intended to explain the symptom of borderline personality disorder experienced by Anna are the instability in her mood and behavior and the fear of abandonment and the instability in her interpersonal relationships This study is conducted using a qualitative design because the data collected and analyzed are in the form of words. The data of this study are narrator’s explanations and the characters’ utterances related the symptoms of the personality disorder suffered by AnnaKey Words: Personality Disorder, Borderline Personality Disorder